2008
DOI: 10.1364/oe.16.001929
|View full text |Cite
|
Sign up to set email alerts
|

Double clad tapered fiber for high power applications

Abstract: We report a novel type of active fiber - tapered double clad fiber suitable for pumping by low brightness sources with large beam parameter product of 50/300 mm x mrad. Ytterbium double clad all-silica fiber (core/1(st) clad/2(nd) clad diameters 27/834/890 mum, NA(core)=0.11, NA(clad)=0.21), tapered down by a factor 4.8 for a length of 10.5 m was drawn from a preform fabricated by plasma chemical technologies. At a moderate Yb-ion concentration and 1:31 core/cladding ratio, the tapered double clad fiber demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(85 citation statements)
references
References 22 publications
3
73
0
4
Order By: Relevance
“…Large core Yb 2 O 3 doped optical fibre plays an important role in the field of high power fibre laser [1,2]. Among the various processes, the solution doping technique is mostly used for incorporation of rare earths (RE) into the silica core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large core Yb 2 O 3 doped optical fibre plays an important role in the field of high power fibre laser [1,2]. Among the various processes, the solution doping technique is mostly used for incorporation of rare earths (RE) into the silica core.…”
Section: Introductionmentioning
confidence: 99%
“…The number of multiple passes under certain flow of a mixture of SiCl 4 and POCl 3 vapour and burner speed are limited by the uniform porosity from one layer to another layer along both axial as well as radial directions. Investigations reported earlier [1,2] were not focused on optimization of the fabrication parameters to overcome the said process limitations. In the present work, we have investigated the critical parameters associated with making of large core Yb 2 O 3 doped fibre preform through deposition of multiple porous core layers by the MCVD technique in combination with the solution doping process and measured the fluorescence spectrum, life time of both preform as well as fibre samples and lasing efficiency of some of the fabricated fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency up-conversion phenomena in trivalent Rare-Earth (RE) ions, hosted in a number of matrixes, have been widely investigated in the past two decades, due to their potential use as visiblewavelength luminescent materials [1][2][3][4][5][6][7][8][9][10][11]. Indeed, Yb 3+ -based upconversion phosphors are thought for applications ranging from biotechnology [1,2] to high power lasers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Yb 3+ -based upconversion phosphors are thought for applications ranging from biotechnology [1,2] to high power lasers [3][4][5]. Since inexpensive near-infrared (NIR) pump sources, such as solid-state lasers and semiconductor laser diodes, are readily available nowadays, all kinds of NIR-to-visible up-conversion emissions and various energy-transfer processes based on the use of Yb 3+ have been investigated [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For a high-power SFS in the 1-μm spectral region [5][6][7][8][9], Schmidt et al [9] reported a narrow-band SFS with maximum output power of 697 W at a center wavelength of 1,030 nm using a two-stage master oscillator power amplifier (MOPA) configuration. In comparison with SFSs in the 1-μm spectral region, few studies have been reported to date on high-power broadband thulium (Tm)-doped SFSs in the 2-µm spectral region [10][11][12].…”
mentioning
confidence: 99%